PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO UNTUK SISWA PENDERITA TUNA NETRA DI SLB- A YAPTI MAKASSAR - Rimba Saputra; Ahmad Rifqi Asrib; Abdul Muis Mappalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
The purpose of this study was to (1) produce audio-based learning media for students with visual impairments at SLB-A YAPTI Makassar, (2) determine the quality of the feasibility of audio-based learning media for students with visual impairments using standard testing ISO/IEC 9126. The type of research used in this research is Research and Development (R&D) using the Research and Development (ADDIE) development model, consisting of 5 (five) stages, namely, analyze (analysis), design (design), develop (development), implement (implementation), and evaluate (evaluation). The subjects in this study were students with visual impairments and teachers at SLB-A YAPTI Makassar. Data were collected through literature study, questionnaires and documentation. The data were analyzed using the ISO/IEC 9126 software testing method which includes aspects of functionality, usability, portability and maintainability. The functionality aspect uses test cases by two system experts, the usability aspect uses a questionnaire, theportability aspect uses various types of smartphones and the maintainability aspect tests the software on the analyzability and changebility aspects. The results of this study are audio-based learning media for students with visual impairments. The results of testing the system functionality aspect are considered good because X is close to 1, the usability aspect gets a score of 65 in the